Philadelphia Paper - The Geology of the North Shore of Lake Superior (Supplementary Note) - T. Sterry Hunt (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
In my address on the " Geognostical Relations of the Metals," delivered before the Institute on the 20th of February last (Vol. I Transactions, p. 331), I spoke of the rocks in the vicinity of Thunder Bay, Lake Superior, where I indicated two series of uncrystalline rocks resting upon the Huronian schists, the lower one consisting of dark-colored argillites and sandstones overlaid, apparently in slight discordance, by nearly horizontal red and white sandstone and marls, which were compared with those of Sault Ste. Marie, and those of the Portage Lake district, on the south shore. These latter sandstones, according to Brooks and Pumpelly, overlie uncomformably the Keweenaw series of copper-bearing amygdaloids, sandstones, and conglomerates, and are in turn overlaid by the Trenton limestone. I then proposed to call this lower series of Thunder Bay, that is to say, the dark-colored argillites and sandstones which are traversed by the silver-bearing lodes of that region, the Animikie group. Shortly after the publication of that address I received an abstract of a paper on the geology of that region by Professor Robert Bell, read before the Montreal Natural History Society, February 24th. He there confirms the statement made in my address that the gold of Lake Shebandowan occurs in the Huronian, which is also seen to be cut by the silver-bearing lodes just mentioned. Professor Bell, in this paper, proposes to designate both what I have called the Animikie group, and the overlying red and white sandstones, by the name of the Nepigon group, for the reason that the upper series is best displayed about Lake Nepigon. This latter series is by Logan supposed to be overlaid by the copper-bearing amygdaloids with conglomerates and sandstones of the north shore (apparently identical with those of Keweenaw); and the whole together, inclnding the Animikie group, constitute his Upper Copper-bearing group. These copper-bearing strata are by him supposed to be overlaid by the red and white sandstones of St. Mary, which are apparently the same with those sandstones which, according to Brooks and Pumpelly, overlie unconformably the similar cupriferous rocks of Portage Lake, and are, in their turn, overlaid by the Trenton limestone. Thus the sandstones which at Thunder Cape overlie the Animikie group are by Logan placed in the midst of the Upper Copper-bear-